IGF-1R Pathway Mediates LQB-118 Antitumoral Activity in Leukemia Resistant Cells - Faria, Fernanda Costas Casal de; Bernardo, Paula Sabbo; Leal, Maria Eduarda Bento; Pinho, Marcos Barcelos de; Netto, Chaquip Daher; Costa, Paulo RR; Maia, Raquel Ciuvalschi (Archives of Clinical and Biomedical Research, 2020)
Chronic myeloid leukemia (CML), a myeloproliferative disorder characterized by the BCR-ABL oncoprotein, presents its treatment based on tyrosine kinase inhibitors (TKIs), mainly imatinib. However, despite its clinical success, almost 30% of all CML patients demand alternative therapy. In this context, the development of drugs capable of overcoming TKIs resistance is imperative. LQB-118 is a compound with anti-tumour effect in two CML cell lines (K562, sensitive and K562-Lucena, resistant) whose mechanism of action is being elucidated. Here, we demonstrate that combined treatment of CML cell lines with imatinib and LQB-118 increased cell death and that microarray analysis of CML cells treated with LQB-118 presented several differentially expressed genes. Also, IGF-1R, AKT and mTOR protein levels are decreased after LQB-118 treatment and the compound alters the expression of all members of miR-29 family. CML cells silenced for IGF-1R were less sensitive to LQB-118 treatment than negative control and protein levels of IGF-1R and AKT were no longer altered after LQB-118 or imatinib treatment. Taken together, our results highlight IGF-1R/AKT/mTOR as a critical axis for LQB-118 activity and demonstrate that LQB-118 is effective in sensitizing CML cells to TKI, contributing to the development of a more efficient therapy.